2017
DOI: 10.1097/md.0000000000005574
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms of CDH1 with nonsyndromic cleft lip with or without cleft palate in a northern Chinese Han population

Abstract: Background:Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a common congenital malformation among live births, and depends on race and ethnic background. The CDH1 gene plays a vital role in orofacial development. Our research was conducted to examine the association between 3 single-nucleotide polymorphisms in the CDH1 gene and NSCL/P.Methods:Three single-nucleotide polymorphisms (rs16260, rs9929218, and rs1801552) of the CDH1 gene were genotyped using the Snapshot mini-sequencing technique in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…With regard to the second polymorphism, the rs1801552-T, a protective association between this variant in homozygous and non-syndromic cleft lip has been reported [ 27 ]. Recent studies indicated that patients with cleft lip had a higher incidence of tumors than the general population [ 28 , 29 ] and, moreover, family members with pathogenetic CDH1 mutation showed a higher incidence of cleft lip/palate than the general population (6–7% versus about 0.1%) [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the second polymorphism, the rs1801552-T, a protective association between this variant in homozygous and non-syndromic cleft lip has been reported [ 27 ]. Recent studies indicated that patients with cleft lip had a higher incidence of tumors than the general population [ 28 , 29 ] and, moreover, family members with pathogenetic CDH1 mutation showed a higher incidence of cleft lip/palate than the general population (6–7% versus about 0.1%) [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of other cell-cell adhesion proteins, such as E-cadherin (Cdh1), during palatogenesis remain to be elucidated (reviewed in Lough et al, 2017). Mutations in CDH1 have been associated with an increased risk for non-syndromic orofacial clefts in humans (Rafighdoost et al, 2013; Vogelaar et al, 2013; Bureau et al, 2014; Hozyasz et al, 2014; Brito et al, 2015; Ittiwut et al, 2016; Song et al, 2017). In mouse models, Cdh1 knockout is embryonic lethal and mutant embryos do not develop beyond E10.5 (Garcia-Higuera et al, 2008).…”
Section: Crosstalk Between Wnt Signaling Cell Adhesion Molecules Andmentioning
confidence: 99%
“…Strongly supporting this role, the destruction of periderm with a cell‐autonomous toxin leads to cleft palate in mouse (Richardson et al, ). Of note, variation near two other genes expressed in periderm, KRT18 and CDH1 , is also associated with risk OFC risk genes (Ittiwut et al, ; Leslie et al, ; Song et al, ). Genes encoding additional members of the gene regulatory network governing periderm differentiation are candidates to harbor mutations that cause or influence risk OFC (see KLF4 below).…”
Section: Use Of Zebrafish To Explore the Developmental Functions Of Gmentioning
confidence: 99%